THE EFFECT OF QUIZ ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT ON GRADE 8 SMP NEGERI 2 BERINGIN - Imelda Anastasya Pasaribu; Christina N Saragi; Harpen Silitonga; Beslina A Siagian (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The aim of this research is to find out the effect of using quiz to increase students’ achievement in writing descriptive text at eight grade students. This research conducted at SMP Negeri 2 Beringin, Jalan Dusun II Kebun Sayur I, Sidodadi Ramunia, Kecamatan Beringin, Kabupaten Deli Serdang. The population of this research was the eight grade students of the academic year 2022/2023. The researcher used experimental quantitative research. The sources data in this research is the eighth grade students at SMP Negeri 2 Beringin. The total sample for this research is 40 students, which are 20 students (VIII-1) in experimental class and 20 students (VIII-2) in control class. Each group was given a pre-test and post-test. The collecting data was done through writing descriptive test. The result showed by t-test (t-observation) was also higher that t-table at the level of significant ? = 0,05. T-observation (2.12) > t-table (2.02). It means give quiz gave significantly affect into students writing skill in descriptive text.